(untitled) (Journal of history, 2020)
In describing the structure of the image of the world in the worldview of the Turkic peoples, it is important to study the mythologies in the legends and heroic songs of the Altaians. The article analyzes the field materials collected during the project implementation in the territory of the Altai Republic and reveals historical relationships between the traditions of oral literature of the Central Asian peoples of the heroic epochs of the Altaians.the mythological stories in the songs of the Altai batyrs were compared with the stories of Russian written monuments and Kazakh myths. During the field expedition, we were able to restore the description of the structure of the image of the world in the worldview of the Turkic peoples in the process of selecting a legend. Mythological prose demonstrated archaic mythological and religious ideas of the Altaians about the surrounding world, natural and social reality. In this context, we should note the complexity of the space-time worldview of the Turks, in this sense, we can not clearly speak about the simplicity of objects in the world. Comparative analysis of Altaic myths with Kazakh myths leads to the conclusion that the ancient Turks perceived themselves as an integral part of the world. According to the ancient Turkic worldview, we will note that people and nature appear as an integral part of the existence of the world, they justify the worldview philosophy about the culture of ecological attitude to the environment, respect for nature, the cosmos and its laws, the peculiarities of the relationship of nature, society and man.